Location of the 11 bp exon in the chicken pro alpha 2(I) collagen gene. - Aho, S (1984)
During the fine structural analysis of the 5' end of the 38 kb chicken pro alpha 2(I) collagen gene, we failed to locate an exon, only 11 bp in size, which had been predicted from the DNA sequence analysis of a cDNA clone complementary to the 5' end of the pro alpha 2(I) collagen mRNA (1). We know report the location of this 11 bp exon, exon 2, at the 5' end of a 180 bp Pst I fragment, 1900 bp 3' to exon 1 and 600 bp 5' to exon 3. Its sequence, ATGTGAGTGAG, is highly unusual in that it contains two overlapping consensus donor splice sequences. Moreover, it is flanked by two overlapping donor splice sequences but only one of the four splice sequences is actually spliced (1). The first half of intron 1 also has an unusual sequence: it is 68% GC, contains 88 CpG dinucleotides and 11 Hpa II sites. The second half is more like other intron sequences in the collagen gene with a GC content of 41%, 19 CpG, and no Hpa II sites. However it contains two sequences with 7 and 9 bp homology to the 14 bp SV40 enhancer core sequence. It is suggested that some part of intron 1 may be involved in regulation.